A Database on the Passage and Enactment of Recent State Minimum Wage Increases - Jeffrey Clemens; Duncan Hobbs; Michael R. Strain (Institute of Labor Economics (IZA), 2018)
This paper presents a dataset that tracks effective minimum wage rates across the U.S. states, including the District of Columbia, from January 1, 2011 to January 1, 2018. We link minimum wage changes to their underlying legislation or ballot initiative and document key dates in their legislative histories. The key dates we track include the dates on which each measure was approved by the legislature, signed by the state governor, or passed via ballot initiative. We then calculate lags between the date on which each minimum wage increase was approved and the date on which it came into effect. Comparing minimum wage increases implemented via ballot initiative to those passed by state legislatures, we find that minimum wage increases enacted through legislation tend to have longer lags to the first increase, longer lags to the last scheduled increase, smaller initial increases, and larger total increases than minimum wage increases approved by ballot initiative.
Keywords: J08; J38; 330; minimum wage; inflation indexing; legislative history